Construction and testing of frames with glued laminated timber with tie-rod (Research, Society and Development, 2022)
The civil construction industry consumes a large amount of natural resources, generating a lot of waste and being responsible for a considerable part of worldwide environmental impacts. The use of timber in structures in civil and agricultural construction resurfaces as a more acceptable solution considering it’s a renewable material for structures and other building parts. Furthermore, the use of wood in a permanent form contributes with the reduction of carbon emissions in the atmosphere, the objective of the present study was a manufacture and test glulam frames with steel cables to evaluate its application as a structural member in poultry farm building. Four reduced scale glulam frames with 1.9 m spam, 1.83 m column and a 3/8” diameter threaded steel bar as a cable under tension were manufactured. The material used in the frames were wood from the species Pinus sp, and a two-component adhesive based on vegetables oils. The mean ultimate load of the testes frames was about 1.37 times the design load. Furthermore, the displacement development observer in the tests was approximately linear even the loads were high. The value obtained for the Pearson correlation coefficient between the apparent wood density and the frame’s strehngth was 0.95. Finally, the results of the study indicate that the use of a steel cable in the frames improved the mechanical behavior regarding structural strength and stiffness.